Step-change in supraglacial pond area on Tshojo Glacier, Bhutan, and potential downstream inundation patterns due to pond drainage events - J. Rachel Carr; Amy Barrett; Sonam Rinzin; Caroline Taylor (Journal of Glaciology)
Climate change is causing Himalayan glaciers to shrink rapidly and natural hazards to increase, while downstream exposure is growing. Glacier shrinkage promotes the formation of glacial lakes, which can suddenly drain and produce glacier lake outburst floods (GLOFs). Bhutan is one of the most vulnerable countries globally to these hazards. Here we use remotely sensed imagery to quantify changes in supraglacial water storage on Tshojo Glacier, Bhutan, where previous supraglacial pond drainage events have necessitated downstream evacuation. Results showed a doubling of both total ponded area (104 529 m2 to 213 943 m2) and its std dev. (64 808 m2 to 158 550 m2) between the periods 1987–2003 and 2007–2020, which was predominantly driven by increases in the areas of the biggest ponds. These ponds drained regularly and have occupied the same location since at least 1967. Tshojo Glacier has remained in the first stage of proglacial lake development for 53 years, which we attribute to its moderate slopes and ice velocities. Numerical modelling shows that pond outbursts can reach between ~6 and 47 km downstream, impacting the remote settlement of Lunana. Our results highlight the need to better quantify variability in supraglacial water storage and its potential to generate GLOFs, as climate warms.